Świat słowiańskich bóstw i ich wpływ na dziecięcego czytelnika (na przykładzie wybranych utworów ze zbioru Priče iz davnine Ivany Brlić Mažuranić) - Sagało, Monika (Motywy fauny i flory w literaturze i kulturze, 2018)
Ivana Brlić Mažuranić published her collection of stories for children titled Priče iz davnine in 1916. In this piece of work the main characters are deities known from Slavic mythology. Domaći, Stribor, Zora-djevojka or Svarožić are some of the characters that accompany people in their daily life. Some of them help people, while others subject them to trials, but first of all, they allow people to discover the truth about themselves and become happy. Reading such stories young readers can find out what rules they should follow their lives. Furthermore, pieces of work like the one presented herein can help to develop people’s interest in ancient beliefs and their national culture.